Enhanced Resting-State Functional Connectivity With Decreased Amplitude of Low-Frequency Fluctuations of the Salience Network in Mindfulness Novices - Gan, Quan; Ding, Ning; Bi, Guoli; Liu, Ruixiang; Zhao, Xingrong; Zhong, Jingmei; Wu, Shaoyuan; Zeng, Yong; Cui, Liqian; Wu, Kunhua; Fu, Yunfa; Chen, Zhuangfei (Frontiers in Human Neuroscience, 2022)
Mindfulness and accordant interventions are often used as complementary treatments with psychological, or psychosomatic problems. It has also been gradually integrated into daily lives for the promotion of psychological well-being in nonclinical populations. The experience of mindful acceptance in a nonjudgmental way brought about the state which less interfered by negative affect. Mindfulness practice often begins with focused attention (FA) meditation, restricted to an inner experience. We postulate that, the brain areas related to interoceptive function would demonstrate intrinsic functional change after mindfulness training for the mindful novices, along with paying more attention to internal processes. To further explore the influence of mindfulness on the organization of brain regions, functional connectivity in voxel and region of interest (ROI) level were both calculated. In the current study, thirty-two healthy volunteers, without any meditation experiences, were enrolled and randomly assigned to a mindfulness-based stress reduction group (MBSR) or control group (CON). Participants in the MBSR group completed 8-weeks of Mindfulness-Based Stress Reduction (MBSR) and rated their mindfulness skills both before and after MBSR. All subjects were evaluated via resting-state functional magnetic resonance imaging in both baselines and after 8 weeks. They also completed a self-report measure of their state and trait anxiety, as well as positive and negative affect. Pre- and post-MBSR assessments revealed decreased ALFF in the right anterior cingulate gyrus (ACC.R), left anterior and posterior insula (aIC.L, pIC.L) as well as the left superior medial frontal gyrus (SFGmed.L) in MBSR practitioners. Strengthened functional connectivity between ACC.R and aIC.R was observed. The mean ALFF values of those regions were inversely positively linked to newly acquired mindful abilities. Together with a decreased negative affect score, our results suggest that brain regions related to attention and interoceptive function were involved at the beginning of mindfulness. This study provides new clues in elucidating when evaluating the brain mechanisms of mindfulness novices.